Branding Strategy and AI-Driven Content Marketing to Increase the Competitiveness of Banana Cake MSMEs in Polewali Mandar Regency - Novy NRA Mokobombang; Fadliyani Nawir; Tyanita Puti Marindah Wardhani; Indrabayu -; Elly Warni; Mukarramah Yusuf; A. Ais Prayogie Alimuddin; Muhammad Abdillah Rahmat; Arliyanti Nurdin; Herlina Anwar; Nadia Indriani Sumardi; Shalomi AE Peter; Muhammad Nashwan Indrabayu; Haerul Algifari; Ratry Mutmainnah (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2026)
UMKM Bolu Pisang Rezky in Polewali Mandar, West Sulawesi Province faces challenges in market visibility and competitiveness in the digital era. The product enjoys strong local market acceptance, yet marketing relies on word-of-mouth referrals, and the existing Facebook account remains inactive. A Community Service (PKM) program "Bolu Pisang Go Digital" was conducted on April 17, 2026, by the Department of Informatics Engineering, Faculty of Engineering, Universitas Hasanuddin. The program aimed to improve MSME actors practical skills in brand identity development and the use of various generative AI platforms for text, image, and video as marketing content tools. The workshop was attended by 9 participants and evaluated via pre-test and post-test (10 multiple-choice questions + 5 Likert-scale statements). Mean scores improved from 87.5 (pre) to 91.1 (post), with participants in the Very Good category increasing from 44.4% to 77.8%. Mean Section B scores (attitude and AI adoption readiness) improved from 4.54 to 4.87 per item. These findings suggest that hands-on generative AI workshops effectively improve the digital literacy of local MSME actors.